LEVEL OF ALBUMIN IN MALARIA AND HIV CO INFECTED PREGNANT WOMEN, ATTENDING THE ANTENATAL CLINIC OF NNAMDI AZIKIWE UNIVERSITY TEACHING HOSPITAL, NNEWI, SOUTH EASTERN NIGERIA - G.C, Emeka; C.E., Ugwu; I.P., Ezeugwunne (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
The purpose of the study was to measure the amount of albumin in pregnant HIV-positive malaria-infected women. Participants in the study were 18 to 40 (36.98 + 5.49) years old, HIV stage 1 and 2 seropositive pregnant women. 80 HIV-positive pregnant women with 40 co-infected with malaria and 80 HIV-negative pregnant women with 40 coinfected with malaria comprised the participant groups. Blood samples were obtained from the subjects for malaria parasite identification using the thick and thin film methods, and HIV status determination using the immunochromatographic approach. The bromocresol green albumin binding method was used to measure the amount of albumin, and the resultant solution was measured spectrophotometrically at 628 nm. In all cases, there was a statistically significant difference in albumin levels between the HIV seronegative group with and without malaria infection (p<0.05) and HIV seropositive group with malaria infection. The mean albumin level of HIV-positive pregnant women who have malaria infection was statistically higher than that of HIV-positive pregnant women who do not have malaria but statistically lower than those of HIV-negative pregnant women with and without malaria infection. The study suggests that pregnant HIV-positive women do not experience a decrease in albumin levels because of malaria infection.